A review of the emerging pandemic of obesity in preschool children in Egypt: Exclusive breastfeeding is protective - Al-Jawaldeh, Ayoub; Abul-Fadl, Azza (Indian Journal of Child Health, 2021)
Introduction: Early exclusive breastfeeding (EBF) without foods or formula milk (FM) is recommended for the first six months of life, for optimum growth and development. Aim: This study aims to review studies in Egypt on nutritional status of preschool children by type of feeding. Methods: A two staged study was done: First; research was obtained from the Egyptian university libraries consortium (www.eulc.edu) on overweight, obesity stunting, and wasting in preschool children. We filtered 18 thesis fitting the criteria of the study. Next, analysis was done to compare EBF versus FM. Results: Comparison of nutritional status of children aged 6–59 months among formula versus EBF was as follows: Overweight 5.4% versus 3.45%, obesity 13.8% versus 5.65%, stunting 21.6% versus 1.15%, and wasting 9.7% versus 0.85%, respectively. Obesity and overweight were higher in males, whereas stunting and wasting were higher in females irrespective of mode of feeding. Early and extended formula feeding, foods before 6 months of life, packed foods, canned drinks, and low activity are risk factors for obesity. Colostrum feeding, exclusive and longer duration of breastfeeding, healthy food intake, and fruits and vegetables are protective. Studies report that deficiency of micronutrients is common with obesity. Conclusions: Prolonged formula feeding and unhealthy food intake are risk factors for the emerging and growing problem of obesity. Policies and legislations are needed to encourage exclusive breastfeeding and control marketing of unhealthy foods.